In Vitro Activity of Oral Antimicrobial Agents against Pathogens Associated with Community-Acquired Upper Respiratory Tract and Urinary Tract Infections: A Five Country Surveillance Study. Issue 2 (June 2016) - Biedenbach, Douglas; Badal, Robert; Huang, Ming-Yi; Motyl, Mary; Singhal, Puneet; Kozlov, Roman; Roman, Arthur; Marcella, Stephen
Abstract Introduction Bacterial infections that cause community-acquired urinary tract infections (CA-UTI) and upper respiratory tract infections (CA-URTI) are most frequently treated empirically. However, an increase in antimicrobial resistance has become a problem when treating outpatients. Methods This study determined the in vitro activities of oral antibiotics among 1501 pathogens from outpatients with CA-UTI and CA-URTI in medical centers during 2012 and 2013 from Argentina, Mexico, Venezuela, Russia, and the Philippines. Minimal inhibitory concentrations (MICs) were determined using broth microdilution and susceptibility defined by Clinical Laboratory Standards Institute (CLSI) and European Committee for Antimicrobial Susceptibility Testing (EUCAST) criteria. Results Ceftibuten (MIC50, ≤0.25 mg/L) was more potent in vitro compared to other β-lactams againstEnterobacteriaceae from CA-UTI. Susceptibility to fluoroquinolones using CLSI criteria varied: Argentina and Mexico (50%), the Philippines (60%), Venezuela (70%), and Russia (80%). Fosfomycin susceptibility was >90% againstEnterobacteriaceae in each country. Susceptibility amongEnterobacteriaceae to trimethoprim-sulfamethoxazole was 30.6–75.6% and nitrofurantoin susceptibility also varied among the countries and was higher when EUCAST breakpoints were applied (65–>90%) compared to CLSI (52–84%). AllHaemophilus influenzae isolates from CA-URTI were susceptible to ceftibuten, cefixime, cefpodoxime, and cefuroxime using CLSI breakpoint criteria. EUCAST criteria produced intermediate and resistant MIC values for these oral cephalosporins. Country-specific susceptibility variation for fluoroquinolones, macrolides, and trimethoprim-sulfamethoxazole was observed amongStreptococcus pneumoniae andStreptococcus pyogenes from CA-URTI. Conclusion This study demonstrated that antimicrobial susceptibility patterns varied in the five countries investigated among pathogens from CA-UTI and CA-URTI. Funding Merck & Co. Inc., Kenilworth, New Jersey, USA.